Effect of varying irrigation schedules and fertility levels on water saving and yield of hybrid rice (Oryza sativa) - CHANDRA, DINESH; KHAN, A R; BEHERA, M S; ANAND, P S B; GHOSH, S; PANDA, D K (The Indian Journal of Agricultural Sciences, 2011)
Field experiments was conducted during 1998–2003 to study the effect of water saving practices for hybrid rice (Oryza sativa L.) under varing fertility management practices. To explore possibility of commercial cultivation of hybrid rice in coasta1 region of eastern India (Orissa state), 3 sets of field experiments were conducted on hybrid rice with different fertility levels and irrigation regimes. The experiments were carried out in dry season of 2002 using hybrid rice ‘PHB 71’ and in wet season of 2003 using hybrid rice ‘CRHR 7’. Irrigating the crop with only 7 cm depth of water once in a week was found detrimental for hybrid rice productivity during dry season. During wet season 2003, beneficial effects were reported in respect of grain yield due to continuous submergence in the field through out the growing season. The interaction of irrigation regimes × N levels showed that higher N level responded only when the hybrid rice maintained continuous submergence. In general, increasing level of fertility increased the grain yield of rice in both experiments.